Recent changes in the clinical features of patients with new psychoactive‐substances‐related disorders in Japan: Comparison of the Nationwide Mental Hospital Surveys on Drug‐related Psychiatric Disorders undertaken in 2012 and 2014. Issue 12 (29th September 2016) - Matsumoto, Toshihiko; Tachimori, Hisateru; Takano, Ayumi; Tanibuchi, Yuko; Funada, Daisuke; Wada, Kiyoshi
Abstract : Aim: The aim of this study was to examine changes in the psychosocial backgrounds and clinical features of patients with psychiatric disorders associated with new psychoactive substances (NPS) between 2012 and 2014 in Japan. Methods: Clinical features of patients with NPS‐related disorders were compared using data from the Nationwide Mental Hospital Surveys on Drug‐related Psychiatric Disorders undertaken in 2012 and 2014. NPS patients were compared with a control group comprising patients with methamphetamine‐related disorders, using data from the same period. Results: In NPS patients, changes were observed in the following three areas between 2012 and 2014: (i) a decrease in the number of employed patients; (ii) an increase in the ratio of patients diagnosed with dependence syndrome; and (iii) a decrease in the ratio of patients diagnosed with psychotic disorder. In methamphetamine patients, only one change was observed: protective custody or arrest record relating to the Pharmaceutical Affairs Act. Conclusion: This study suggests that the number of patients dependent upon NPS, and those exhibiting social dysfunction, increased between 2012 and 2014. There is a need to focus future measures against NPS dependence: not only on stopping the supply of drugs, but also on reducing the demand for them.